2015
DOI: 10.1038/cddiscovery.2015.21
|View full text |Cite
|
Sign up to set email alerts
|

Tumor suppressor Nf2/merlin drives Schwann cell changes following electromagnetic field exposure through Hippo-dependent mechanisms

Abstract: Previous evidence showed mutations of the neurofibromin type 2 gene (Nf2), encoding the tumor suppressor protein merlin, in sporadic and vestibular schwannomas affecting Schwann cells (SCs). Accordingly, efforts have been addressed to identify possible factors, even environmental, that may regulate neurofibromas growth. In this context, we investigated the exposure of SC to an electromagnetic field (EMF), which is an environmental issue modulating biological processes. Here, we show that SC exposed to 50 Hz EM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…At the third in vitro passage, SCs were treated for 48 h with 4 μM forskolin, then used for different assays. SC purity (more than 98%) was tested with a specific antibody against glycoprotein P0 [ 30 ]. Phase-contrast images of DRG neurons and SCs in vitro cultures are provided in Supplementary Figure S2…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the third in vitro passage, SCs were treated for 48 h with 4 μM forskolin, then used for different assays. SC purity (more than 98%) was tested with a specific antibody against glycoprotein P0 [ 30 ]. Phase-contrast images of DRG neurons and SCs in vitro cultures are provided in Supplementary Figure S2…”
Section: Methodsmentioning
confidence: 99%
“…DRG neurons were characterized by immunofluorescence for neurofilament of 200 kDa (NF200, Sigma-Aldrich), as described [14,29]. SCs cultures were obtained as previously described [14,30]. Sciatic nerves were digested with 1% collagenase and 0.25% trypsin (Sigma-Aldrich), then mechanically dissociated, filtered through a 100 µm filter (BD Biosciences) and centrifuged 5 min at 900 rpm.…”
Section: Sensory Neurons and Scs Primary Culturesmentioning
confidence: 99%
“…The most notables are YAP and TAZ, two transcriptional activators of the Hippo pathway. Indeed, several works have shown that YAP can be activated through the Hippo pathway in SCs by Crb/Amolt proteins (Colciago et al, 2015 ; Fernando et al, 2016 ). In addition, mechanical stimulation through a signaling cascade involving FAK, Src, PI3K, JNK pathways (Codelia et al, 2014 ; Mohseni et al, 2014 ; Kim and Gumbiner, 2015 ; Elbediwy et al, 2016 ), or formation of actomyosin filaments and presence of F-actin (Dupont et al, 2011 ; Aragona et al, 2013 ) can regulate YAP and TAZ.…”
Section: Extracellular and Intracellular Components Of Sc Mechanobiolmentioning
confidence: 99%
“…Less studied, the stimulation of SCs by electromagnetic fields also opens interesting perspectives in peripheral nerve regeneration (Sisken et al, 1989 ; Kanje, 1992 ). Indeed, application of an electromagnetic field to cultured SCs promotes their proliferation and migration, presumably through YAP/TAZ (Colciago et al, 2015 ). Finally, physical therapy has also been considered as a therapeutic approach to stimulate tensile strain on peripheral nerves.…”
Section: Using Sc Mechanobiology In Therapeutic Approaches For Periphmentioning
confidence: 99%
“…Mechanical stimulation can regulate YAP/TAZ through signals involving FAK, Src, PI3K and JNK pathways (Codelia et al, 2014; Mohseni et al, 2014; Kim and Gumbiner, 2015; Elbediwy et al, 2016), or the formation of actomyosin filaments and accumulation of F-actin (Dupont et al, 2011; Aragona et al, 2013). In addition, YAP/TAZ in SCs can be activated through Crb/Amolt proteins and laminin/G-protein signaling (Colciago et al, 2015; Fernando et al, 2016; Poitelon et al, 2016; Deng et al, 2017). YAP/TAZ regulate gene expression by binding to other DNA-binding transcription factors, especially TEAD transcription factors, but also p73, ERBB4, EGR-1 SMADs RUNXs and TBX5 (Kim et al, 2018).…”
Section: Introductionmentioning
confidence: 99%